El concepto de legitimidad como sucedáneo de la justicia política (2016)
This paper seeks to explore within Schmittian legal thought, receipt of the Aristotelian concept of political justice in his Thomist interpretation. To this end, the author establishes the interdependence of the concepts of legitimacy and obedience and compares the concept of obedience in the Thomist reception of Aristotle with the concept of obedience in Schmitt, who seeks to transcend legal positivism in his search for an effective legal system. Then, it develops the relationship between the concept of legitimacy proposed by the German philosopher and jurist and types of legitimacy in St. Thomas. Finally, it analyzes the respective link to the concept of legitimacy with the effectiveness of existing powers in the Constitution of the Republic of Weimar.